Человеческий потенциал стран мира и его динамика - Чернецкий, Ю.А. (Інститут демографії та соціальних досліджень НАН України, 2006)
Охарактеризовано понятие человеческого потенциала экономики, в отличие от понятия трудовых ресурсов. Представлены анализ глобальной демографической ситуации и тенденций, авторская классификация экономик по величине индекса развития человеческого потенциала, рейтинг стран мира по объёму человеческого потенциала за 2002 г. и основные модели динамики ИРЧП. The concept of the human potential of an economy, as different from the concept of the labour force, is characterised. The analysis of global demographic situation and trends, the author’s classification of the world’s economies by their human development indexes, their rating by the volume of human potential in 2002 and main models of the HDI dynamics are presented.